Enhanced Contractive Tension and Upregulated Muscarinic Receptor 2/3 in Colorectum Contribute to Constipation in 6-Hydroxydopamine-Induced Parkinson’s Disease Rats - Zhang, Xiao-Li; Zhang, Xiao-Hui; Yu, Xiao; Zheng, Li-Fei; Feng, Xiao-Yan; Liu, Chen-Zhe; Quan, Zhu-Sheng; Zhang, Yue; Zhu, Jin-Xia (Frontiers in Aging Neuroscience, 2021)
Constipation and defecatory dysfunctions are frequent symptoms in patients with Parkinson’s disease (PD). The pathology of Lewy bodies in colonic and rectal cholinergic neurons suggests that cholinergic pathways are involved in colorectal dysmotility in PD. However, the underlying mechanism is unclear. The aim of the present study is to examine the effect of central dopaminergic denervation in rats, induced by injection 6-hydroxydopamine into the bilateral substania nigra (6-OHDA rats), on colorectal contractive activity, content of acetylcholine (ACh), vasoactive intestinal peptide (VIP) and expression of neural nitric oxide synthase (nNOS) and muscarinic receptor (MR). Strain gauge force transducers combined with electrical field stimulation (EFS), gut transit time, immunohistochemistry, ELISA, western blot and ultraperformance liquid chromatography tandem mass spectrometry were used in this study. The 6-OHDA rats exhibited outlet obstruction constipation characterized by prolonged transit time, enhanced contractive tension and fecal retention in colorectum. Pretreatment with tetrodotoxin significantly increased the colorectal motility. EFS-induced cholinergic contractions were diminished in the colorectum. Bethanechol chloride promoted colorectal motility in a dose-dependent manner, and much stronger reactivity of bethanechol chloride was observed in 6-OHDA rats. The ACh, VIP and protein expression of nNOS was decreased, but M2R and M3R were notably upregulated in colorectal muscularis externa. Moreover, the number of cholinergic neurons was reduced in sacral parasympathetic nucleus (SPN) of 6-OHDA rats. In conclusion, central nigrostriatal dopaminergic denervation is associated with decreased cholinergic neurons in SPN, decreased ACh, VIP content, and nNOS expression and upregulated M2R and M3R in colorectum, resulting in colorectal dysmotility, which contributes to outlet obstruction constipation. The study provides new insights into the mechanism of constipation and potential therapeutic targets for constipation in PD patients.